Alpha II Antiplasmin Deficiency Complicating Pregnancy: A Case Report - Brenda Dawley (Obstetrics and Gynecology International)
Background. Alpha II antiplasmin is a protein involved in the inhibition of fibrinolysis. A deficiency in this protein leads to increased hemorrhage. It is inherited in an autosomal recessive fashion. Case. 30-year-old Gravida 1, Para 0, presented for prenatal care with her first and subsequently her second pregnancy. Her medical history was significant for a known deficiency in alpha II antiplasmin. Her first and second pregnancies were complicated by nonobstetrical hemorrhage requiring transfusions and severe preeclampsia requiring preterm deliveries. Conclusion. Alpha II antiplasmin deficiency resulted in multiple episodes of nonobstetrical hemorrhages requiring transfusion and ultimately preterm deliveries due to severe preeclampsia. Both infants and mother had a good outcome. The presence of this disorder may require a multidisciplinary team approach involving obstetricians, pediatricians, and hematologists. Precis. Alpha II antiplasmin deficiency is a rare autosomal recessive disorder leading to increased fibrinolysis and hemorrhage. We present a case report of a pregnancy complicated by this disorder.